Pengembangan Komik dengan Pendekatan Culturally Responsive Teaching untuk Menumbuhkan Literasi Sains pada Kelas V SDN Kalicari 01 Semarang - Priyangga, Brian; Mushafanah, Qoriati; Listyarini, Ikha; Kristanti, Dewi Natalia (Jurnal Kridatama Sains dan Teknologi, 2023)
This research is a comic development with a Culturally Responsive Teaching approach to foster scientific literacy. Learning media can help achieve learning objectives. This study aims to develop amusing learning media with a Culturally Responsive Teaching approach to foster scientific literacy in fifth-grade elementary schools. The type of research used is Research and Development with the ADDIE development model, namely Analyze, Design, Development, Implementation, and Evaluation. This study used test subjects by carrying out validity tests on media experts, material experts, learning experts, and the responses of ten fifth-grade elementary school students—data collection using a questionnaire instrument. Research data were analyzed through descriptive quantitative and descriptive qualitative. The results of the media expert validator are categorized as very valid. The results of the material expert validator are classified as very accurate. The results of the expert learning validator are categorized as very accurate as well as the results of the responses of ten fifth-grade elementary school students who were categorized as very valid. The overall results of the validator test are can be used as an alternative for teachers in adding a variety of learning media, it can increase understanding of concepts because the media helps students in improving scientific attitudes, remembering material and learning is more fun in class V SD. Keywords: ADDIE, media expert, scientific literacy, natural science.